Newborn Screening Knowledge and Attitudes Among Midwives and Out-of-Hospital-Birth Parents. Issue 4 (October 2020) - Coupal, Elena; Hart, Kim; Wong, Bob; Rothwell, Erin
Abstract : Midwifery and nursing are collaborative partners in both education and practice. Understanding needs and barriers to clinical services such as newborn screening is essential. This study examined knowledge and attitudes of midwives and out-of-hospital-birth parents about newborn blood spot screening (NBS). Descriptive and cross-sectional surveys were distributed to midwives and out-of-hospital-birth parents from birth center registries and the Utah Health Department of Vital Records. Seventeen midwife surveys (response rate: 17%) and 113 parent surveys (response rate: 31%) were returned. Most midwives and out-of-hospital-birth parents reported satisfactory knowledge scores about NBS. Only 5% of parents ( n = 6) did not participate in NBS. Most midwives reported that NBS is important and encouraged patients to consider undergoing NBS. Some concerns included the lack of education for both midwives and out-of-hospital patients and the trauma and accuracy of the heel prick soon after birth. Both midwives and out-of-hospital-birth parents expressed a need for improved NBS education. Additional studies are needed to ascertain whether this trend is seen with similar populations throughout the United States, to further elucidate the factors that drive NBS nonparticipation, and to develop educational resources for midwives and their patients.